Penggunaam Komik Digital Berbasis Problem Based Learning Pada Mahasiswa Akuntansi - Laila Rossana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
21st-century learning is directed at the optimal use of technology and information. Optimal use of information technology is intended to improve student's critical thinking skills and work readiness. However, in reality, using learning media for accounting students is not optimal so learning feels boring. The purpose of this study was to determine the effectiveness of using digital comics based on Problem-Based Learning (PBL) to improve critical thinking skills and work readiness of accounting students. This study used an experimental research method, with a pretest-posttest control group design. Based on the results of the study, showed that the use of digital comic media based on PBL was effective in improving students' work readiness and critical thinking skills.